New records of polymorphism in Asian libellulid dragonflies (Insecta: Odonata). Issue 4 (1st October 2020) - Joshi, Shantanu; Poorten, Nancy van der; Sumanapala, Amila; Nielsen, Erland; Patel, Jenis; Nielsen, Bo; Sawant, Dattaprasad; Sherif, Muhamed
Abstract : Polymorphism has rarely been reported from dragonflies of the Libellulidae (Odonata: Anisoptera) family. Here, we report female-limited polymorphism in females of five species of the Libellulidae and a gynandromorph male of Brachythemis contaminata from South Asia . We describe the morphological variation between andromorph and heteromorph females, and collate records of andromorph females from various sources. Yearly number of andromorph females of Crocothemis servilia, Urothemis signata and Neurothemis tullia was calculated using records from published literature and unpublished sources, and social media.